SELF-REGULATED LEARNING AND SOCIAL SUPPORT AS PREDICTORS OF CAREER MATURITY - Tanjung, Pangihutan Syepriady; Fadilah, Risydah; Lubis, Suaidah (Pena Cendekia Insani, 2026)
This study examined the influence of self-regulated learning and social support on students’ career maturity. A quantitative design was applied to 132 high school students using psychological scales and analyzed through multiple linear regression. The results showed that self-regulated learning had a positive and significant effect on career maturity (? = 0.785; t = 8.504; p < 0.001), while social support also had a positive and significant effect (? = 0.332; t = 2.671; p = 0.009). Simultaneously, both variables significantly influenced career maturity (F = 90.920; p < 0.001) with a contribution of 58.5% (R² = 0.585). These findings indicate that self-regulated learning is the dominant predictor of career maturity compared to social support. In conclusion, the development of students’ career maturity is more strongly determined by internal readiness through self-regulated learning than by external support alone.